Evaluation of Fitness and Health Centres by Dropout Members - Georgios Zarotis (New Ideas Concerning Arts and Social Studies Vol. 2, 2025)
For many years, the number of fitness clubs has been almost stagnating. The fitness line is also marked by an annual fluctuation of total membership numbers. High customer fluctuation, however, significantly complicates long-term financial and staff-wise arrangements. No matter the fitness club setting contended that to foster loyalty, workout programs need to consider the variety of demands. The aim of the study is to examine if and to what extent the evaluations of fitness studios by persons who have recently resigned from their membership are related to general studio conditions such as studio atmosphere, facilities, trainer’s competence and other features. In other words, the question is whether there are typical prioritizations on positive or negative evaluations by dropouts from fitness sport. In the survey, a total of 225 people, who had quit their membership in the past, were questioned in a telephone inquiry. The study was conducted in a health-oriented fitness centre in a major city in Germany. At the time of the study, the fitness facility had up to 1.151 memberships. Among them, 59% of the members were women and 41% were men. The average age of the respondents was 43.5 years. The average duration of membership added up to 4.4 years. The respondents were persons who had terminated their contract in the period between July 2015 and July 2016. In this period, 305 members departed, of whom 225 persons were found and questioned. A variance analysis with measurement repetition factor is calculated to ensure the inferential statistic of the differences between studio evaluations. Overall, the various aspects of the studio offer and its surroundings were mostly rated as “good”. The respondents appreciated particularly the coaches (friendliness, helpfulness, competence), followed by opening hours, trial training and the first impression. The membership costs and individual aspects such as space, music and ventilation are assessed more critically, if not really badly. A quality concept should always be formulated from the customer’s point of view; it must focus on the customer and their specific goals. The data show that the various evaluation aspects were clearly assessed differently by the respondents, and that there was apparently little generalised information on the studio evaluation. The increasing awareness and determination of people to proactively take care of their health represent a promising basis for the future development of the sector.